Home admission in COVID times: challenge for the actions of the nursing professional - Dayamí Guerra Villalpanda (Medisur)
A very common method of care in the community is home admission, widely practiced during the COVID-19 pandemic, in which the family doctor and nurse were required to visit diagnosed patients daily at home. But, due to the increase in cases, it was not really possible to visit all the admissions. Given this fact, the nursing staff imposed a challenge on their professional performance, which included technical preparation, especially when performing the physical examination, emphasizing auscultation, since the respiratory system is the most affected in the patient sick from COVID. The objective of this article is to make considerations that express the author`s point of view who considers home admissions to sick patients with COVID-19 a challenge in the performance of nursing staff.